9x-4y9 /-3x-3y-2 Need help.
1 answer:
<span><span>y9)
((9•(x-4))•—————————————)•y(-2)
-(3)(-3)x(-3)
</span><span>Simplify —-(3)(-3)x(-3) </span></span><span><span>((9 • (x-4)) • -27x3y9) • y(-2)
</span></span><span>(32x(-4) • -27x3y9) • y(-2)
</span> x(-4) multiplied by x3 = x((-4) + 3) = x(-1) = 1/x1 = 1/x 32 multiplied by 33 = 3(2 + 3) = 35<span> -35x(-1)y9 • y(-2) </span>y9 multiplied by y(-2) = y(9 + (-2)) = y7<span>
</span>Final result :<span> -35x(-1)y7
</span>I believe this is the answer :) ( pls tell me if I am wrong and have a great day!)
You might be interested in
I think you have multiply 5x4 which equals 20 then 20 divided by 10 which equals 2 and that’s ur answer
(-2 + 0.8) ÷ (1²-1.3) =
(-1.2) ÷ (1-1.3)
(-1.2) ÷ (-0.3)
= 4
Answer:
63
Step-by-step explanation:
hhehehehhehehehehh hope this helps
A. 9 and 7+2x
B. 1 and 2 respectively.
C. 2 from 2x